The butterfly clues - Ellison, Kate. (New York : Egmont USA, 2013)
Penelope "Lo" Marin copes with the stress of constantly moving by collecting--sometimes stealing--things from each new place, a habit that has become more compulsive since the death of her brother, but while she is wandering around Cleveland, Ohio, Lo finds a butterfly pendant at a flea market she recognizes as something stolen from a recently murdered girl and begins to piece together clues to find out the truth behind her death.
Booklist starred
School Library Journal starred
Wilson's Senior High School
Booklist starred, March 2012
Bulletin (Center for Children's books), April 2012
Horn Book, November 2012
Keywords: Death -- Juvenile fiction; Murder -- Juvenile fiction; Obsessive-compulsive disorder -- Juvenile fiction; Death -- Fiction; Murder -- Fiction; Mystery and detective stories; Obsessive-compulsive disorder -- Fiction; Death -- Fiction; Homicide -- Fiction; Mystery fiction; Obsessive-compulsive disorder -- Fiction; Cleveland (Ohio) -- Juvenile fiction; Cleveland (Ohio) -- Fiction; Cleveland (Ohio) -- Fiction; Mystery fiction